2007
DOI: 10.1128/jvi.01518-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Uracil-DNA Glycosylase Activity of Epstein-Barr Virus BKRF3 and Its Role in Lytic Viral DNA Replication

Abstract: Uracil-DNA glycosylases (UDGs) of the uracil-N-glycosylase (UNG) family are the primary DNA repair enzymes responsible for removal of inappropriate uracil from DNA. Recent studies further suggest that the nuclear human UNG2 and the UDGs of large DNA viruses may coordinate with their DNA polymerase accessory factors to enhance DNA replication. Based on its amino acid sequence, the putative UDG of Epstein-Barr virus (EBV), BKRF3, belongs to the UNG family of proteins, and it was demonstrated previously to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 79 publications
2
43
0
Order By: Relevance
“…However, HSV-1 reactivation was measured post-explant from trigeminal ganglia: a tissue composed of terminally differentiated adult neurons with low levels of host UNG (18,36). Reactivation is also reduced in human gammaherpesvirus latency cell systems lacking the EBV viral UNG (BKRF3) alone or in the absence of both the vUNG and the host UNG (13,18,(37)(38)(39). Interestingly, Su et al (13) recently reported that host UNG2 levels decrease as EBV reactivation proceeds, indicating that the viral UNG is needed to promote replication under conditions of low host UNG levels (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, HSV-1 reactivation was measured post-explant from trigeminal ganglia: a tissue composed of terminally differentiated adult neurons with low levels of host UNG (18,36). Reactivation is also reduced in human gammaherpesvirus latency cell systems lacking the EBV viral UNG (BKRF3) alone or in the absence of both the vUNG and the host UNG (13,18,(37)(38)(39). Interestingly, Su et al (13) recently reported that host UNG2 levels decrease as EBV reactivation proceeds, indicating that the viral UNG is needed to promote replication under conditions of low host UNG levels (13).…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as described previously (47). To detect the EBV lytic proteins, the primary antibodies used were laboratory-made mouse anti-BKRF3 serum 3, mouse anti-Zta 1B4, anti-Rta 467, anti-BGLF4 2616, and anti-BMRF 88A9, as described previously (4,48). The BALF2 antibody (OT13B) was kindly provided by J. M. Middeldorp (49).…”
Section: Methodsmentioning
confidence: 99%
“…Subcellular fractionation. The subcellular fractionation protocol was modified from a previous study (4). Briefly, trypsinized cells were harvested, washed, and incubated with 1 ml hypotonic buffer (5 mM TrisHCl, pH 7.4, 5 mM KCl, 1.5 mM MgCl 2 , 0.1 mM EGTA, 1 mM dithiothreitol [DTT], and 1 mM phenylmethylsulfonyl fluoride [PMSF]) with gentle shaking at 4°C for 1 h. The cell suspension then was passed 15 times through a 26-gauge needle and centrifuged at 500 ϫ g at 4°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations